Discalced Carmelites as Focus of Attention of Polish People’s Republic Security Force in Cracow Voivodship in the Light of Preserved Reports Sent to Ministry of Public Security and Ministry of Internal Affairs in the Years 1947-1970 - Józef Marecki (Folia Historica Cracoviensia, 2004)
In the times of the Polish People’s Republic, national security issues and, at the same time, surveillance of the society and suppression of many institutions – the Catholic Church included - were in the hands of appropriate services, modelled on the Soviet NKVD. At first this was the Ministry of Public Security and since 1956 the Security Police. The first part of the article presents the organization of security units in the voivodship of Cracow and the distribution of monastic communities, while the second throws light on the activities of these units uh the basis of preserved reports sent from Cracow to the Ministry of Public Security and the Ministry of Internal Affairs. Officials of the Security Police who worked in the voivodship and district departments took a close interest in the Discalced Carmelite monks, taking account of their wartime past, pastoral activity and connections with the Church hierarchy. To ensure influence upon the life of the Discalced Carmelite Province as well as access to information on monastic internal issues they gained several secret collaborators within the congregation itself and its lay associates. The article is the first attempt at showing the methods of the Security Police (SB) and the Security Office (UB) activities directed at monastic orders; methods aiming at subjugating to the authorities not only the orders themselves, but the whole Catholic Church in Poland.